2020
DOI: 10.1590/s1517-707620200004.1185
|View full text |Cite
|
Sign up to set email alerts
|

Adsorção de azul de metileno em hidrocarvões de resíduos têxteis

Abstract: RESUMO Os produtos têxteis, cada vez mais presentes em nosso dia-a-dia, geram uma grande quantidade de resíduos, sejam eles de forma sólida ou líquida. Dar o destino correto ou até mesmo transformar os resíduos sólidos é o novo desafio a ser enfrentado. Os resíduos sólidos, geralmente retalhos de tecidos, contém grande quantidade de compostos orgânicos, que podem ser carbonizados. Neste contexto, o principal objetivo do presente estudo foi a síntese de hidrocarvão utilizando resíduos têxteis. Os hidrocarvões f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
0
2
0
3
Order By: Relevance
“…It is observed that during the process where there is a reduction of the peak at 1450 cm -1 , the dehydration reaction occurs, which is characteristic of the hydrothermal carbonization technique and the main reaction for the success of the synthesis [6]. The functional groups detected in the adsorbents have a strong carbon content, which is in line with the technique used as well as with the raw material, which has the characteristic of having high carbon contents.…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 78%
“…It is observed that during the process where there is a reduction of the peak at 1450 cm -1 , the dehydration reaction occurs, which is characteristic of the hydrothermal carbonization technique and the main reaction for the success of the synthesis [6]. The functional groups detected in the adsorbents have a strong carbon content, which is in line with the technique used as well as with the raw material, which has the characteristic of having high carbon contents.…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 78%
“…∆H less than zero proved that the adsorption process of MB was exothermic. Furthermore, a performance comparison of adsorption effect on MB adsorption between the resulted functional adsorbent FS-N-2M-2 h-293K and previously reported adsorbents has been depicted in Table 6 [51][52][53][54][55]. The results of the analyses revealed that the novel functional adsorbent gains advantage over many other adsorbents, indicating that FS-N-2M-2 h-293K is a potential promising strategy for the treatment of MB wastewater.…”
Section: Adsorption Thermodynamicsmentioning
confidence: 95%
“…Lai et al (2019) Estudar a aplicação do grafeno em materiais tridimensionais objetivando a adsorção de tintas e metais pesados. Lima et al (2020) Analisar a adsorção de azul de metileno frente à hidrocarvões de resíduos têxteis. Martins et al (2018) Elaborar modelos computacionais para estudar a aplicação de nanocompósitos de TiO 2 /Grafeno em aplicações fotocatalíticas.…”
Section: Ferreira (2015)unclassified
“…Nesse quesito, os materiais que se mostraram promissores de acordo com a literatura foram os hidrocarvões, onde considerando-se os parâmetros das isotermas de adsorção de Langmuir, o hidrocarvão de resíduo têxtil apresentou capacidade adsortiva de aproximadamente 140,35 mg.g -1 . Outros materiais da mesma categoria como o hidrocarvão ativado com NaOH de casca de coco e hidrocarvão de resíduos de acerola apresentaram também considerável capacidade de adsorção, sendo 108,8 mg.g -¹ e 107,0 mg.g -¹, respectivamente (Lima et al, 2020). É válido salientar também que a casca de coco é um material lignocelulósico, isto é, um biomaterial que possui em sua composição a celulose, as hemiceluloses e as ligninas, e que por conta desse fator apresenta capacidade adsortiva (Ferreira, 2015).…”
Section: Aplicações Do Grafeno Para O Meio Ambienteunclassified